The Hepatoprotective Effect of Omega-7 Against Paracetamol-Induced Hepatotoxicity in Male Rats - Hadeel Ali Hameed; Ali Faris Hassan (College of Pharmacy University of Baghdad, 2023)
Abstract Paracetamol toxicity, whether accidental or not is a worldwide issue that leads to hepatotoxicity, acute liver failure, as well as irreversible liver injury requiring liver transplantation. Omega-7 is a monounsaturated fatty acid with a number of beneficial properties. The aim of the present study was to assess the potential protective role of omega-7 fatty acid against hepatotoxicity induced by paracetamol in male rats. Thirty male Rats were separated into five groups (six rats in each group) and received the following treatment: group 1 received liquid paraffin orally via gavage tube for seven days successively, group 2 received liquid paraffin  orally via gavage tube for seven days successively, and on day eight, rats received a single intraperitoneal injection of paracetamol (500 mg/kg/day), group 3 received omega-7 (300 mg/kg/day) orally via gavage tube for seven days successively, group 4 received omega-7 (100 mg/kg/day) orally via gavage tube for seven days successively, and on day eight, rats received a single intraperitoneal injection of paracetamol (500 mg/kg/day), group 5 received omega-7 (300 mg/kg/day) orally via gavage tube for seven days successively, and on day eight, rats received a single intraperitoneal injection of paracetamol (500 mg/kg/day). On day nine, rats have been sacrificed by cervical dislocation and liver homogenate samples were collected for analysis. This study showed that there was a significant decrease in hepatic superoxide dismutase, catalase, glutathione-peroxidase and glutathione levels, accompanied with significant increase in hepatic malondialdehyde level in paracetamol group compared to the negative control group. However, administration of omega-7 resulted in significant increase in hepatic superoxide dismutase, catalase and glutathione levels and significant decrease in hepatic malondialdehyde level compared to paracetamol group. In conclusion, omega-7 has a protective effect on paracetamol-induced hepatotoxicity in rats. Keywords: Antioxidant, Hepatotoxicity, Omega-7, Oxidative stress, Paracetamol.